Nickel-framed film with alternate layers of nickel and silicon for high performance lithium ion battery anodes - Karahan, Billur Deniz (Elsevier Science, 2020)
The present work reports for the first time in the open literature the formation of 4-mu m thick film with alternate layers of nickel and silicon by the magnetron sputtering method. Of the two kinds of samples prepared, the first is composed of alternate nanometer thick (<15 nm) Ni rich and Si rich layers. Employing a novel conceptual design to further improve the film's mechanical properties, a second sample is produced in which additional Ni rich layers (60 nm thick) are deposited over each micron thick of Ni/Si bilayers.The morphological, structural, mechanical and electrochemical test results show that silicon in the coating increases the capacity of the electrode and Ni atoms that are electrochemically inactive versus Li create conductive pathways throughout the film section. In the film design, the high diffusion rate of Ni in Si leads to the formation of amorphous solid solution which improves the reversibility of the lithiation/delithiation reactions. Additionally, the presence of 60 nm thick Ni rich layers works as 'skelton' to maintain the integrity of the coating upon cycling, and hence increases the electro-mechanical resistance of the negative electrode. Due to this new design the stress-strain distribution in the coating is improved such that sample 2 delivers 881 mA h g(-1) discharge capacity even at high current loads of 500 mA g(-1) (with 80% 1st cycle coulombic efficiency) after 300 cycles. This outstanding performance of the metallic framed layered film is believed to hold a great prospect for designing electrodes of the next generation high energy density batteries. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Layered Film; Magnetron Sputtering; Negative Electrode; Lithium Ion Batteries; Silicon Thin Films